Preliminary Study Rearing of Oryzias sp. from Tunda Island, Indonesia, Under Laboratory Condition - Muh. Herjayanto; Annisa Misykah Mauliddina; Esa Rama Widiyawan; Nugroho Agung Prasetyo; Lukman Anugrah Agung; Magfira Magfira; Abdul Gani (Musamus Fisheries and Marine Journal, 2019)
Oryzias sp. from Tunda Island, Indonesia has the potential as a model organism in laboratories and also ornamental fish. Basic information regarding maintenance during adaptation post-transportation from its habitat in nature, embryo incubation and maintenance of larvae is needed as a basis for breeding activities. The results showed that Oryzias sp. from Tunda Island can adapt, spawning and produce a total 262 eggs (diameter 0.88-1.02 mm) in a controlled environment. Eggs from spawning in nature begin to hatch on the 11th incubation day, the hatching peak occurs on the 13th day with a hatching process 4-9 days at 25-27oC. The hatching rate ranges from 57.14-100% and the survival of 5 days old lavae after hatching is 72.72-100.00%. The transportation technique in this study has not been able to suppress fish mortality during post-transportation rearing.